2017
DOI: 10.7759/cureus.1844
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Approaches in Obesity and Metabolic Syndrome Associated with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a pathophysiological disorder affecting reproductive and metabolic indices. PCOS is commonly associated with a high prevalence of insulin resistance and obesity; this association carries an increased risk of developing metabolic syndrome, type 2 diabetes mellitus (T2DM), and cardiovascular disease. Guidelines recommend lifestyle modification, metformin, hormonal contraceptives (HCs), and bariatric surgery as the main treatment options in obese patients with PCOS. Studies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 44 publications
0
46
0
4
Order By: Relevance
“…Berberine, if associated with a healthy lifestyle, improves women's body composition and causes androgen's reduction as pointed out by Saleem et al [3,8].…”
Section: Purposementioning
confidence: 97%
See 1 more Smart Citation
“…Berberine, if associated with a healthy lifestyle, improves women's body composition and causes androgen's reduction as pointed out by Saleem et al [3,8].…”
Section: Purposementioning
confidence: 97%
“…Berberine is also shown to be effective against insulin resistance and obesity, particularly against visceral adipose tissue in vitro and in murine models [2,7,8].…”
Section: Purposementioning
confidence: 99%
“…3,11,12 Pharmacological treatments address various aspects of PCOS, including insulin resistance (e.g., metformin and pioglitazone), menstrual abnormalities, hirsutism, and acne (e.g., hormonal contraceptives), endocrine-metabolic disorders (e.g., inositols), and obesity (e.g., orlistat), among others. 13 Presently available obesity drugs have raised safety concerns due to unknown teratogenic effects among reproductive-age women. 10 In contrast, current evidence supports bariatric surgery as more effective than nonsurgical treatments at achieving sustained weight loss, while mitigating obesity-related health problems, including type 2 diabetes, hypertension, dyslipidemia, metabolic syndrome, sleep apnea, and osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with PCOS, lifestyle modification, medication, and weight-loss surgery are also the main medical therapies in managing overweight/obesity and preventing metabolic comorbidities. 9 Yet, sustained, significant weight loss is difficult to achieve with these interventions or is frequently complicated by significant side-effects. Thus, development of a safe and effective body weight-control strategy is an important medical need for patients with PCOS.…”
mentioning
confidence: 99%
“…The use of acupuncture for overweight/obese individuals with PCOS has been a long-standing practice in Chinese medicine, and a systematic review suggested that acupuncture has favorable effects in overweight patients who have PCOS. 9 In a 2016 trial of 17 overweight women with PCOS, 5 weeks of electroacupuncture (EA) treatment improved glucose regulation and adipose tissue androgens. 10 In contrast to exercise, EA improved insulin sensitivity and modulated adipose tissue gene expression without influencing adipose tissue in a rat PCOS model.…”
mentioning
confidence: 99%